2015
DOI: 10.1016/j.neurobiolaging.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of p75 neurotrophin receptor ameliorates the cognitive deficits in a model of Alzheimer's disease

Abstract: a b s t r a c tAlzheimer's disease (AD) is an extremely prevalent cause of dementia. It is characterized by progressive memory loss, confusion, and other behavioral and physiological problems. The amyloid-b (Ab) protein is thought to be involved in the pathogenesis of AD, and there is evidence that Ab may act through the p75 neurotrophin receptor (p75) to mediate its pathogenic effects. This raises the possibility that reducing levels of p75 could be a treatment for AD by preventing the effects of Ab. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Indeed, we have reported previously (Fortress et al, 2011 ) that a single intra-hippocampal proNGF injection in aged rats induces morphological changes in basal forebrain cholinergic neurons, with dendritic retraction and atrophy of cell bodies. Recent studies also showed that a reduction of p75NTR expression ameliorates the cognitive deficits (Murphy et al, 2015 ) and increases cholinergic innervation in the dentate gyrus (Dokter et al, 2015 ), basolateral amygdala (Busch et al, 2017 ) and visual cortex (Von Bohlen und Halbach and Von Bohlen und Halbach, 2016 ); moreover, a small molecule ligand of p75NTR (LM11A-31) reverses cholinergic neurite dystrophy in Alzheimer’s Disease mouse models (Simmons et al, 2014 ). Therefore, we cannot exclude that the improvement of spatial learning and memory in TAT-Pep5 infused mice reflects positive effects on basal forebrain cholinergic neurons and their hippocampal projections.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, we have reported previously (Fortress et al, 2011 ) that a single intra-hippocampal proNGF injection in aged rats induces morphological changes in basal forebrain cholinergic neurons, with dendritic retraction and atrophy of cell bodies. Recent studies also showed that a reduction of p75NTR expression ameliorates the cognitive deficits (Murphy et al, 2015 ) and increases cholinergic innervation in the dentate gyrus (Dokter et al, 2015 ), basolateral amygdala (Busch et al, 2017 ) and visual cortex (Von Bohlen und Halbach and Von Bohlen und Halbach, 2016 ); moreover, a small molecule ligand of p75NTR (LM11A-31) reverses cholinergic neurite dystrophy in Alzheimer’s Disease mouse models (Simmons et al, 2014 ). Therefore, we cannot exclude that the improvement of spatial learning and memory in TAT-Pep5 infused mice reflects positive effects on basal forebrain cholinergic neurons and their hippocampal projections.…”
Section: Discussionmentioning
confidence: 98%
“…Through either its constitutive activity in the unliganded state, or via that stimulated by its proneurotropin (proNT) ligands, p75 NTR promotes degenerative signaling mechanisms including activation of JNK, caspase, and RhoA (Casaccia-Bonnefil et al, 1996; Harrington et al, 2002; Troy et al, 2002; Ibanez and Simi, 2012; Coulson and Nykjaer, 2013) each of which likely contributes to AD-related degeneration (Figure 12). Crossing various AD mouse models with a p75 NTR knockout mouse construct results in reduced neuronal degeneration (Sotthibundhu et al, 2008; Knowles et al, 2009; Murphy et al, 2015). Multiple studies have identified genetic polymorphisms in the genes encoding p75 NTR , proNGF, proBDNF, or p75 NTR co-receptors including sortilin and SorCS2 that mediate proNT binding associated with increased AD risk (Cozza et al, 2008; Di Maria et al, 2012; Anastasia et al, 2013; Reitz et al, 2013; Andersson et al, 2016; Matyi et al, 2017).…”
Section: Small Molecule Neurotrophin Compounds For Treatment Of Admentioning
confidence: 99%
“…In vivo knock down of p75 NTR increased ChAT activity in aging rats ( Barrett et al, 2016 ). The reduction of p75 NTR expression ameliorated cognitive and cholinergic deficits in Tg2576 mice ( Murphy et al, 2015 ).…”
Section: Acetyl-coa Levels In the Brainmentioning
confidence: 99%